Pelatihan Pemanfaatan Limbah Botol Bekas Dan Koran Sebagai Media Pembelajaran Yang Kreatif - Irwansyah Suwahyu; Ninik Rahayu Ashadi; Muhammad Asriadi; Ismail Aqsha; Muhammad Haristo Rahman (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
This PKM is about PKM Training on the use of used bottle waste and newspapers as creative learning media at SMPN 4 Bajeng. The problem faced by these partners is that waste bottles and newspapers around the students' area are not used as waste. Students are less sensitive to the potential in their environment, causing them not to have many ideas about creative learning media, one of which is the use of used bottles and newspapers. Students receive training on the use of waste bottles and newspapers from competent parties in making creative learning media. The solution offered by the service team is to conduct training on the use of used bottles and newspapers as creative learning media. In implementing this PKM program, the speakers presented are from educational circles, both lecturers and teachers who are capable of developing their profession, especially the use of waste bottles and newspapers as creative learning media: (1) Welcoming the service team from Makassar State University by the principal of SMP 4 Bajeng, (2) Material provision activities, (3) Mentoring and evaluation of class X students at SMP 4 Bajeng. Training methods are lecture methods, question and answer methods, and training/practice methods.